1989
DOI: 10.2330/joralbiosci1965.31.240
|View full text |Cite
|
Sign up to set email alerts
|

Self-setting apatite cement. VI. Possibility as bone substitute.

Abstract: Abstract:Self-setting apatite cement was investigated to evaluate its use as a possible bone substitute in the rat femur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…A number of studies have reported methods for reducing the setting time of CPC, for example by addition of OHAp seed crystals in CPC [8] and by controlling the particle sizes of CPC ingredients [9]. Results from these studies showed that the setting times can be shortened somewhat but not significantly.…”
Section: Introductionmentioning
confidence: 96%
“…A number of studies have reported methods for reducing the setting time of CPC, for example by addition of OHAp seed crystals in CPC [8] and by controlling the particle sizes of CPC ingredients [9]. Results from these studies showed that the setting times can be shortened somewhat but not significantly.…”
Section: Introductionmentioning
confidence: 96%
“…2H20 or DCPD], or MCPM [Ca(H2PO4)2" H20] to form hydroxyapatite [Calo-x(HPO4)~,(PO¢)6-0, (OH)2 -x where 0 _< x _< 1 or HAp] did not reach completion within clinically relevant periods of time without the use of accelerators [1][2][3][4]. Typically the kinetics and setting time of these reactions are accelerated [4][5][6][7][8][9][10][11][12] by the addition of either large proportions of HAp filler and/or by accelerating the reaction using acidic solutions (phosphoric acid, acetic acid, maleic acid, etc. ).…”
Section: Introductionmentioning
confidence: 99%
“…While a number of studies have investigated strength development and/or setting times of CPCs containing TetCP and DCP/DCPD [4,5,7,9,14,16] an in-depth investigation and interpretation of the kinetics of these types of reactions has not been reported. The present investigation describes reactions between TetCP and DCPD proportioned to form both calcium deficient (Ca/P = 1.50) and stoichiometric (Ca/P--1.67) HAp.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the £-ray-sterilized samples, the non-sterilized cement showed a fracture surface morphology that is smoother and denser. As mentioned earlier, the strength of a CPC is often determined by multiple factors, such as apatite content, 26) porosity level 5) and cement morphology. 27) Since the £-raysterilized and non-sterilized samples of the present study had similar porosity values, the observed higher strength in nonsterilized samples is considered primarily due to their denser morphology and aforementioned higher apatite conversion ratio.…”
Section: Effect Of Gamma Radiation On Properties Of a Calcium Phosphamentioning
confidence: 99%